Resolución de problemas y el aprendizaje de la matemática en niños de la Institución Educativa Inicial N°62012 Santa Rosa de Lima, Yurimaguas 2024 - Carrillo Chaves, Eva (2025)
The objective of this research was to examine the relationship between the application of problem solving and the learning of mathematics in children of the Institución Educativa Inicial N°62012 Santa Rosa de Lima, in Yurimaguas, during the year 2024. This research was developed with a quantitative approach, adopting a non-experimental, correlational and transectional design. The sample was made up of a total of 107 children from the aforementioned institution. For data collection, the observation technique was used, using a structured observation guide as an instrument. The validity of the instrument was ensured through an evaluation carried out by a group of experts with extensive experience in the area. The results obtained validated the main hypothesis of the research, showing a significant relationship between the application of problem solving and mathematics learning. The moderate-high correlation (Tau-b = 0,641, p < 0,05) revealed that, as children develop more effective problem-solving strategies, their mathematics performance also improves. In summary, the findings of this study provide strong evidence supporting the idea that problem solving is a fundamental element in the mathematical learning process.